Exploratory Spatial Data Analysis Using Geoda for Regional Apparatus in Malang Regency - Suci Astutik; Maria Bernadetha Theresia Mitakda; Darmanto Darmanto; Wulaida Rizky Fitrilia; Ismi Chai Runnisa; Diego Irsandy; Nisa Dwirahma Widhiasih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2023)
The Malang Regency Communication and Information Office (Diskominfo) since 2019 has published the Malang Regency One Data book. Some KMSD data contain location information which is referred to as spatial data. The Malang Regency Communication and Information Office (Diskominfo) since 2019 has published the Malang Regency One Data book. Some KMSD data contain location information which is referred to as spatial data. However, the problem faced by Diskominfo is the limited Human Resources both Diskominfo and data producers (OPD) in exploring sectoral data involving spatial data and presenting it in a map. The purpose of this activity is to provide training in exploratory spatial data analysis for OPD to improve sectoral data processing capabilities, especially those containing spatial information. The training was conducted through the provision of materials and discussions on exploratory spatial data analysis and its application using the Geoda software.